Compressibility Behaviour On Carbonation of Ground Granulated Blast Furnace Slag (GGBS) Treated Kaolin - Basarom, Norsyahidah; Ayub, Azimah; Mohd Yunus, Nor Zurairahetty; Abang Hasbollah, Dayang Zulaikha; Zolkepli, Muhammad Farhan; Zainuddin, Nurul Eilmy (Journal of Sustainable Underground Exploration, 2023)
With the growing worry over pollution in the environment, the necessity to comprehend this phenomenon has multiplied. Not only that, the economic gain made in the last decade, along with the fast growth of the world population, has come at a huge environmental cost. One of the never-ending issues is carbon dioxide emission and notably, the construction sector is no exception to mean to contribute through many development activities. Therefore, this study focuses on the compressibility behaviour of Ground Granulated Blast Furnace Slag (GGBS) treated kaolin clay due to carbonation. This study discusses the effect of carbonation on GGBS-treated kaolin as an effort to use sustainable materials which able to improve the geotechnical properties of soil and safe to say, help to reduce the emission of CO2. Testing program via one-dimensional consolidation test found that the compressibility characteristics improved as increased the GGBS content. Overall, the results illustrate that higher GGBS content and longer curing period gives lower compressibility characteristic. It was also found that the carbonated kaolin sample further improve the compressibility characteristics as compared to ambient condition of treated kaolin sample. In conclusion, GGBS can improve the compressibility characteristic of kaolin with carbonation consideration.